Inflation and Nominal Rigidities in Spanish Regions: The Ball and Mankiw Approach - Carlos Usabiaga; María Ángeles Caraballo (European Regional Science Association (ERSA), 2004)
In this work we centre on the menu cost models of new keynesian economics and, more concretely, on the empirical testing line proposed by Ball and Mankiw (1994, 1995), authors that confront in a monopolistic competition model the explanation of why a shock that affects relative prices also affects mean inflation. Their conclusion is that if mean inflation is near to zero the inflation-skewness relation is stronger than the inflation-variability relation, whereas in the case of a high mean inflation the inflation-variability relation is stronger. Following their approach in our analysis mean inflation is the explained variable, whereas skewness and variability of the distribution of price changes are the main explanatory variables. Our type of analysis has different applications. Firstly, in the case that we confront a relative price shock, if variability and skewness, or some of their transformations, affect inflation it means that our economy is vulnerable, so it makes especially difficult to control inflation. A second application refers to a feasible way to measure core inflation, eliminating from inflation the transitory effects introduced by skewness. Finally, this approach can contribute to test if downward price rigidity is an exogenous phenomenon or the response of optimizing agents that confront menu costs in an inflationary context. Despite these utilities, the Ball and Mankiw (1995) approximation has been rarely applied to Spanish economy.In essence, our work tries to answer whether menu costs à la Ball and Mankiw are plausible for Spanish economy, and whether exists homogeneity of the Spanish regions at this respect. The structure of the work is the following: a) exposition of the basic data and variables, the methodology followed, and the results of our first approximation to Ball and Mankiw (1995); b) consideration of alternative measures of variability and skewness; c) analysis of the role of kurtosis and introduction of two real variables (unemployment and production) as control variables; d) analysis of the causality problem; and e) after the analysis at regional level, we study whether the regions jointly present an homogeneous behavior in this area. Our period of analysis is 1994.01-2001.12. We have chosen this low inflation period because around an annual 4-5% is placed the upper limit for which the model predicts a strong inflation-skewness relation. The essential data that we use come from the series of monthly variation rate of consumer price index, disaggregated by regions and goods and services (33 subgroups), elaborated by the Instituto Nacional de Estadística (INE). In general, we observe an homogeneous behavior of the "structure" of inflation for the Spanish regions. Our analysis corroborates the results of Ball and Mankiw (1995) about the importance of the skewness of the distribution of price changes. Their results in the line that the variability coefficient is higher than the skewness coefficient, and that the estimations containing skewness present a higher coefficient of determination are also confirmed. The significance of skewness and variability at regional level shows the vulnerability of Spanish inflation in terms of relative price shocks.
Keywords: 330